Enhanced GP training – a spiral of learning. Issue 1 (January 2013) - Simon, Chantal; Riley, Ben
The RCGP believes that an enhanced and extended GP training programme is a necessary way to equip new GPs for their future NHS roles, but how will that be delivered? This article describes the spiral model of incremental skill acquisition and application that enhanced and extended GP training will use for the new 4-year GP specialty training programme. As GPs travel from their early general practice experience towards their roles as fully fledged independently practising 'expert generalists', they will gain a firm foundation of skills, honed to the general practice environment.